Analisis Emisi CH4 dan Potensi Energi dari Tempat Pembuangan Akhir (TPA) Muara Fajar 2 Kota Pekanbaru - Sasmita, Aryo; Asmura, Jecky; Nurmaida, Betharia (Universitas Trunojoyo Madura, 2022)
The city of Pekanbaru as an economic center and a destination for urbanization in Riau province has also experienced an increase in population. This is the cause of the increase in the amount of waste that enters the Muara Fajar 2 TPA Pekanbaru City. Solid waste that is stockpiled in the TPA undergoes a degradation process resulting in greenhouse gases in the form of CH4 which contribute to global warming, but have the potential to be utilized as alternative energy. The purpose of this study was to calculate CH4 emissions from landfilling activities at TPA 2 Muara Fajar Pekanbaru City and the potential energy produced. The method for calculating landfill gas emissions uses the IPCC 2019 method. The amount of waste that goes to the TPA in 2011-2020 is obtained from the Pekanbaru City Environment and Forestry Office. The highest estimated values of CH4 gas emissions resulting from landfilling activities at the Muara Fajar 2 TPA Pekanbaru City occurred in 2049 with CH4 emissions of 34,847 Mg/year and CH4 volume of 48,560,479 m3/year. The daily electricity generated is 52,052.84 kWh which can meet the electricity needs of 9,362 households in Pekanbaru City.